Structural controls and 3-D geometry of gold mineraliastion at Consort Gold Mine and along the northern margin of the Archaean Barberton Greenstone Belt, Barberton - Munyai, Mphoyanga Richard (My University, 2011)
The area around New Consort Gold Mine (NCGM) is complexly deformed during at least 5 distinct events named D1NC – D5NC. D1NC - D3NC events involve progressive shearing and folding linked to the 3250-3225 Ma accretionary history of the Barberton greenstone belt (D1NC and D2NC), and subsequent 3105 Ma emplacement and doming of surrounding batholiths (D3NC). During D3NC the area experienced intense strain partitioning with the development of a network of shear zones, which envelop structural domains characterized by locally unique deformation histories. Around NCGM, D3NC events involved early shearing (D3aNC) along the Consort Bar followed by two episodes of 600m scale folding (D3bNC and D3cNC) resulting in a complex fold interference pattern. Pegmatites intruded during D3NC. D4NC structures comprise a network of extensional brittle-ductile shear fractures and associated kink bands and crenulation folds that formed concomitant with gold mineralization after all the D3NC structures had fully developed, marking a clearly separate event. The D4NC fractures are distributed along 100-200m wide corridors as 10-100m scale, enechelon, Riedel, anti-Riedel and P-shear arrays. D5NC structures represent represent late reverse faults of unknown age. The critical structures controlling gold mineralization are the D4NC fracture zones. The distribution of high-grade ore zones is controlled by the intersection orientation of D4NC fractures and suitable host lithologies, mainly the silicified hinge zones of D1NC folds and the laminated chert of the Consort Bar. Because these host lithologies were complexly folded in D1NC-D3bNC-D3cNC fold interference patterns, the 3-D distribution of ore zones is highly discontinuous and complex. Kinematics analysis and stress inversion using Bingham tensor solutions and an optimized dihedron method, of mineralized D4NC fractures along old gold workings at NCGM, consistently indicate a vertical σ1, and a horizontal NW-SE iii directed σ3, within a pure extensional stress regime indicating that gold mineralization occurred in an extensional tectonic setting. Results for the nearby Clutha, Albion and Woodstock mines are similar. This study suggests that gold mineralization in the NCGM area can be linked to an extensional event that may have developed separately from the accretionary events shaping the craton and may have coincided with the opening of Dominion Group basins.